Andrew Ellicott papers - Ellicott, Andrew, 1754-1820.; Gillespie, David
Correspondence, maps, charts, and reports of astronomical observations chiefly concerning Ellicott's work in surveying the boundary between the U.S. and Florida under the San Lorenzo Treaty (1795) and also his surveys of the city of Washington, the boundary between Georgia and South Carolina, the town of Presque Isle (later Erie), Pa., and the boundary between the U.S. and Canada under the Treaty of Ghent (1814). Other subjects discussed are international politics, Indian affairs, and the Blount conspiracy (1797). Includes papers of Ellicott's assistant David Gillespie.
Family correspondents include Ellicott's wife Sarah and his brother Joseph. Other correspondents include Daniel Clark, Jr., William Dunbar, Manuel Gayoso de Lemos, David Gillespie, Benjamin Hawkins, Thomas Jefferson, James Madison, Stephen Minor, Robert Patterson, Timothy Pickering, John Pitchlynn, Winthrop Sargent, Cornelius Peter Van Ness, and James Wilkinson.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Mathematician and surveyor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Blount, William, -- 1749-1800.; Clark, Daniel, -- 1766-1813 -- Correspondence; Dunbar, William, -- 1749-1810 -- Correspondence; Ellicott, Joseph, -- 1760-1826 -- Correspondence; Ellicott, Sarah -- Correspondence; Gayoso de Lemos, Manuel, -- 1747-1799 -- Correspondence; Hawkins, Benjamin, -- 1754-1816 -- Correspondence; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Madison, James, -- 1751-1836 -- Correspondence; Minor, Stephen -- Correspondence; Patterson, Robert, -- 1743-1824 -- Correspondence; Pickering, Timothy, -- 1745-1829 -- Correspondence; Pitchlynn, John, -- approximately 1756-1835 -- Correspondence; Sargent, Winthrop, -- 1753-1820 -- Correspondence; Van Ness, Cornelius P. -- 1782-1852 -- Correspondence; Wilkinson, James, -- 1757-1825 -- Correspondence; San Lorenzo Treaty, 1795.; Great Britain. -- 1814 December 24.; Astronomy; Conspiracies -- United States; Indians of North America -- Government relations; Surveying -- Georgia; Surveying -- Pennsylvania; Surveying -- South Carolina; Surveying -- Washington (D.C.); World politics; Canada -- Boundaries -- United States; Erie (Pa.) -- Surveys; Florida -- Boundaries -- United States; Georgia -- Boundaries -- South Carolina; Georgia -- Surveys; South Carolina -- Boundaries -- Georgia; South Carolina -- Surveys; United States -- Boundaries -- Canada; United States -- Boundaries -- Florida; Washington (D.C.) -- Surveys; Mathematicians; Surveyors